Film Regulation and Convergence of Child Comedy Skits in Online Media Platforms: Implications on Nigerian Child's Rights ACT 2003 - CHIME-NGANYA, Chioma Rosemary; OKANUME, Ben Odili; ONYEJELEM, Timothy Ekeledirichukwu (International Journal of Religion Education and Law, 2026)
The digital revolution has fundamentally altered the intersection of traditional cinema and social media entertainment, creating a hybrid ecosystem where "Hollywood meets Silicon Valley." In Nigeria, this convergence has facilitated the meteoric rise of child comedy skits on decentralized platforms such as YouTube, TikTok, and Instagram. However, this vibrant creative landscape often operates within a "culture of informality" and an ethically deficient "hustle culture" that bypasses established film narrative ethics and regulatory frameworks. Against this background, this study examined film regulation and the convergence of child comedy skits on online media platforms and interrogated the resulting implications for the Nigerian Child’s Rights Act (CRA) 2003. The study adopted a qualitative method, utilizing Textual Analysis to describe and interpret purposively selected child comedy skits and a Systematic Literature Review (SLR) to synthesize statutory documents, scholarly articles, and legal instruments. Findings revealed a profound "regulatory asymmetry," where the high-frequency production enabled by Digital Generative Multimedia Tools (DGMTT) outpaces the monitoring capacity of centralized media authorities such as the National Film and Video Censors Board (NFVCB) and the National Broadcasting Commission (NBC). The study further identified a significant "legislative dissonance," as the CRA 2003 remains anchored in a pre-ubiquitous internet era and fails to specifically address modern digital threats, including online grooming, data privacy violations, and the exploitation of children for viral engagement. Additionally, the study noted that "digital gatekeepers," specifically parents and teachers, frequently lack the digital literacy required to safeguard child actors from cyber insecurity. The study concluded that while media convergence empowers the Nigerian child with performative agency and entrepreneurial opportunities, it simultaneously exposes them to a hazardous and unregulated digital lifeworld. The study recommended an urgent amendment of the Child’s Rights Act 2003 to incorporate specific provisions for online child safety, a collaborative synergy between Nigerian media regulators to establish a unified digital media policy, and the adoption of AI-enhanced monitoring tools to detect digital exploitation. The research uniquely contributes to knowledge by introducing a proactive communication and legal model to safeguard the psychosocial and moral development of children in Nigeria’s evolving science-driven audiovisual ecosystem.